This I Believe - Joy, C. Turner (Charles Turner) (Tufts Archival Research Center, 2006)
Charles Turner, 37th Superintendent of the United States Naval Academy at Annapolis, compares life to a navigation in that everyone begins life in a specific spot and situation and the travels toward an unkown destination, using what ever tools we have acquired in life to give direction; from this he adds that it is important to keep your awareness in the present and do the task at hand. This essay also contains an advertisement for a This I Believe LP album.